Estudio sobre la obligación de contratar trabajadores con discapacidad como condición de ejecución de los contratos celebrados por la Comunidad de Madrid (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2011)
Modern European Society manages respecting series of principles and basic rights like the equality between people and the absence of discrimination. In order to this, the Spanish Legal System has established different regulatory norms —which the jurisprudence has interpreted— concerning the insertion of disabled people in the society. These norms have made it possible for the hiring organs of the Civil Services to demand, in some cases, the obligation of hiring disabled people as a condition of carrying out the contracts which contractors have with them. This study wants to explain the procedure which can be applicable in the Comunidad de Madrid, to declare that if this obligation is not carry out the responsibility belongs to the contractor. To develop this purpose, issues like the form and the procedural moment to assume this obligation and to require the accreditation of its performance, and to make effective the responsibility of its failure of execute, are going to be analysed.